Surface and microstructural analyses of a Roman quadrans dating back to first century ad. (2nd March 2018) - de Ruggiero, A.C.; Kaciulis, S.; Mezzi, A.; Montanari, R.; Soltani, P.; Varone, A.
Abstract : The paper reports the results of the analyses performed on a Roman quadrans dating back to the first centuryad, belonging to a group of more than 8.000 coins found in the bed of river Tiber during an archaeological research in 1987–1988. The quadrans was examined by means of X‐ray diffraction, scanning electron microscopy, energy dispersion spectroscopy, and X‐ray photoelectron spectroscopy. Energy dispersion spectroscopy analytical results confirmed that the coin is made of pure copper. The compounds present in the patina have been identified through X‐ray diffraction. The spectrum is the overlapping of several peaks, and the results show that the patina substantially consists of malachite Cu2 CO3 (OH)2, cupric chloride CuCl2, and nantokite CuCl. X‐ray photoelectron spectroscopy only evidences nantokite because of the different analysis depths of the two techniques. This means that nantokite forms a thin outer layer in the concretion covering the quadrans .